The alignment of the accelerator modules of the Cool Copper Collider C3 with the Rasnik 3-point alignment system - van der Graaf Harry; van Bakel Niels; Bouwens Bram; Breidenbach Martin; Haase Andrew; van Heijningen Joris; Koushik Anoop Nagesh; Nanni Emilio; du Pree Tristan; van Remortel Nick; Vernieri Caterina (EPJ Web of Conferences)
For C3, some 2000 accelerator modules must be 5D positioned, within 10 µm transversal, on a 2.3 km long straight line, for both linacs. In the Rasnik alignment system, light from a point-like monochromatic source falls on a zone lens, forming a Fraunhofer diffraction pattern on an image pixel sensor. The alignment of three objects can be obtained by analyzing the position of the diffraction pattern on the sensor. The alignment of a large number of objects can be realized by fixing a stick on each object, carrying all three Rasnik components. With this leap frog geometry, all sticks are mutually coupled, forming a multipoint alignment system. The system should operate in ambient air, in vacuum, and in liquid nitrogen. Due to the heat dissipation of these components, bubbles are formed, causing an error in the measured alignment when crossing the optical path. Various methods of beam shielding are presented. With the Quarter Cryo Module (QCM), essential studies will be carried out, enabling the realization of C3. The QCM will be equipped with four Rasnik chains, measuring alignment parameters with redundancy. In addition, the bubble-induced vibrations of the accelerator components can be registered accurately.